The Law of international cooperation - Месхія, О. Н. (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2014)
This article presents the scientific and legal analysis of the category of «the right of international cooperation». The issues of the existence in contemporary international law of the general obligation to cooperate have been analyzed. The positivist and natural law approaches to justify the obligation of states to cooperate have been highlighted. The main sources of international law, establishing the obligation of States to cooperate have been pointed out and their critical analyses have been conducted. The cooperation as to international commons has been studied in particular concerning the use and disposal of the international seabed area, Antarctica and outer space.